It rides a pale horse - Marino, Andy, 1980- (Redhook, 2022)
"The Larkin siblings are known around the small town of Wofford Falls. Both are artists, but Peter Larkin, Lark to his friends, is the hometown hero. The one who went to the big city and got famous, then came back and settled down. He's the kind of guy who becomes fast friends with almost anyone. His sister Betsy on the other hand is more...eccentric. She keeps to herself. When Lark goes to deliver one of his latest pieces to a fabulously rich buyer, it seems like a regular transaction. Even being met at the gate of the sprawling, secluded estate by an intimidating security guard seems normal. Until the guard plays him a live feed: Betsy being abducted in real time. Lark is informed that she's safe for now, but her well-being is entirely in his hands. He's given a book. Do what the book says, and Betsy will go free. It seems simple enough. But as Lark begins to read he realizes: the book might be demonic. Its writer may be unhinged. His sister's captors are almost certainly not what they seem. And his town and those within it are...changing. And the only way out is through"--